Address to the Bond Club of New York, May 14, 1969 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, emphasizes that the Bank is a development investment institution, not a philanthropic or social welfare organization. He says the Bank’s lending policy is founded on two basic principles: sound projects and creditworthy borrowers. Loans are not made unless both criteria are met. He discussed hard-loan operations of the IBRD. In the Bank’s 23-year history, there have been no losses on its loans. No government has failed to honor its obligations. The Bank has not been a target for debt repudiation as have bilateral aid agencies and private credit corporations. He says the reason is obvious. Developing nations are convinced that it is in their own best interest to keep impeccable relations with the Bank. He further states that because the Bank’s loans, made out of borrowed funds, are disbursed and repaid in the same currencies, the Bank faces no devaluation risks on its borrowed funds. Its obligations to its creditors are matched by the repayments due from the borrowers. He concludes by saying that the World Bank is unique in its security and strength, and in its purpose and program. In the business of development, hardheaded realism must be the guide. Neither naive optimism, nor despondent pessimism will do. The simple fact is that in the last third of the twentieth century the underdeveloped world will either develop, or it will be caught up in catastrophe. The one thing it will not do is stand still and wait.